2014
DOI: 10.1158/1535-7163.mct-13-0775
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-Mesenchymal Transition Mediates Docetaxel Resistance and High Risk of Relapse in Prostate Cancer

Abstract: Molecular characterization of radical prostatectomy specimens after systemic therapy may identify a gene expression profile for resistance to therapy. This study assessed tumor cells from patients with prostate cancer participating in a phase II neoadjuvant docetaxel and androgen deprivation trial to identify mediators of resistance. Transcriptional level of 93 genes from a docetaxel-resistant prostate cancer cell lines microarray study was analyzed by TaqMan low-density arrays in tumors from patients with hig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
112
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 49 publications
11
112
0
Order By: Relevance
“…The former suggests that there is a fraction of chemoresistant cells in the tumor mass, which initiates tumorigenesis after chemotherapy; the latter emphasizes that the ability of chemoresistance is induced by chemodrugs, manifesting an inevitable result for chemotherapy. Mechanistically, chemoresistance can be ascribed to various reasons including drug inactivation, off-target, cell death inhibition, epigenetics, decreased drug uptake/ increased drug efflux and EMT (30,31). The drug efflux system attracts more and more attentions for its irreplaceable roles in chemoresistance, which is mainly mediated by ABC superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…The former suggests that there is a fraction of chemoresistant cells in the tumor mass, which initiates tumorigenesis after chemotherapy; the latter emphasizes that the ability of chemoresistance is induced by chemodrugs, manifesting an inevitable result for chemotherapy. Mechanistically, chemoresistance can be ascribed to various reasons including drug inactivation, off-target, cell death inhibition, epigenetics, decreased drug uptake/ increased drug efflux and EMT (30,31). The drug efflux system attracts more and more attentions for its irreplaceable roles in chemoresistance, which is mainly mediated by ABC superfamily.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that Dox-resistant PCa cells could express EMT markers and EMT could reverse Dox resistance [15], thus we explored the role of INPP4B in Dox-induced EMT in the study. The results demonstrated that overexpression of INPP4B significantly downregulated the mesenchymal markers fibronectin (Fig.…”
Section: Overexpression Of Inpp4b Affects Emt Makers In Docetaxelresimentioning
confidence: 99%
“…Activation of the EMT program is characterized by the loss of E-cadherin and the gain of mesenchymal markers such as Vimentin and N-cadherin, which increases the migratory ability of the cells and contribute notably to the interaction of tumors cells with the microenvironment at the bone [24][25][26]. Such a phenomenon leads to the activation of a set of transcription factors including Twist and Snail, and is orchestrated by epigenetic remodeling involving the Polycomb complex [27].…”
Section: Androgen Receptor Activity Independent Pathwaymentioning
confidence: 99%